DERIVASI PRINSIP KEHATI-HATIAN DALAM PEMBERIAN KREDIT DALAM PEMBERIAN KREDIT YANG DIJAMIN DENGAN GADAI (STUDI PADA PT PEGADAIAN (Persero) KANWIL I MEDAN) - Sri Hartati Br. Nadapdap; Tan Kamello; Hasim Purba; Dedi Harianto (USU LAW JOURNAL, 2018)
ABSTRACT Prudential principle needs to be applied at PT Pegadaian (Persero) Kanwil I Medan with the aim of preventing a bad credit as well as maintain public confidence towards the existence of this institution as an institution who give credit that is securedby a pledge. The outline of problems which is found in this thesis are how the application of prudential principe in granting of credit secured by the pledge of, how the effectiveness at the application of prudential principle in reducing bad credit which is secured by pledge and the obstacles which is found at the application of prudential principle at PT Pegadaian (Persero) Kanwil I Medan. Method of this researchhas usedthe juridical normative research methods which are analytical and descriptive. This method used a legislation approached with the technique of data collection was library research, supported by doing interviews to some informants in order to obtain more complete and valid informations. The results of this research showed that in applying prudential principle, PT Pegadaian (Persero) Kanwil I Medan is using several legal regulations such as the financial services authority regulation number 01 of the year 2015 about risk management for non banking finance institutions and a few of regulations issued by the board of directors of PT Pegadaian (Persero). This institutions is also forming an internal unit as a way to apply prudential principle effectively. It also found that prudential principle is absolutely mandatory and enforced to be applied before give loans which is secured by a pledge to people.   Keywords : Prudential Principle, Credit, Pawn